Implementasi Algoritma Advanced Encryption Standard (AES) pada Layanan SMS Desa - Intan Fitriani; Aryo Baskoro Utomo (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Along with the development of technology, Short Message Service (SMS) has begun to be used to communicate between someone and the system in an agency. But in some cases, the security of messages sent through the SMS application has not been well protected. To improve data security and confidentiality, cryptographic algorithms with Advanced Encryption Standard (AES) can be done. The method used is the Waterfall method. AES encryption testing is done by comparing the manual calculations and the results of the encryption on the system. Blackbox test, CrackStation test, and Avalanche Effect (AE) test were also carried out. Brute force test results using CrackStation software that ciphertext cannot be solved. And in the avalanche effect (AE) test, the AE value of each 128-bit AES key is 44.53%, 192-bit is 48.44%, and 256-bit is 56.25%. Therefore, 192-bit and 256-bit AES keys are recommended for use because AE values are in the range of 45% - 60%.